Investment in the family: is it beneficial in post-modern society? - Taranowicz, Iwona (Studia Demograficzne, 2020)
We observe very deep changes involving the family. People live in different kinds of partnerships, not only in traditional marriages. They decide to have fewer children or even not have them at all. So is the family still beneficial in post-modern society? This article discusses the contemporary determinant conditions regarding the decision to start a family. The majority of them are connected with the labour market and social processes like inividualisation, changing social ties, and decaying of cultural universe. The post-modern society does not encourage people to start families. However, people still decide to have children and to form stable partnerships. This is because having offspring and a partner will give them something of the highest importance that is invaluable in post-modern society – emotional ties and emotional fulfilment.